Assessing the effect of public policy on worker absenteeism - Per Johansson; Mårten Palme (Institute for Labour Market Policy Evaluation (IFAU), 2001)
We analyze the effect of economic incentives on worker absenteeism, using panel data on work absence for 1990 and 1991 with a sample of 1,396 Swedish blue-collar workers. During this period Sweden implemented major reforms of both its national income replacement program for short-term sickness and income taxes. Both affected the worker's cost of missing work. Our econometric model allows for state-dependent dynamic behavior and control for unobserved heterogeneity. The latter proves to be an important consideration. We find that the cost of being absent significantly affects work absence behavior.
Keywords: J22; 330; Sickness insurance; unobserved heterogeneity; logit regression